A systematic review on the association between ovarian and prostate cancer with BRCA1 and BRCA2 gene - Sarpparajan Chitra Veena; Mohammed Vajagathali; Veerabathiran Ramakrishnan (Сибирский онкологический журнал)
Background. BRCA1 and BRCA2 were discussed as the basis of inherited adenocarcinoma and breast and ovarian malignancy. Ovarian cancer is uncommon in women below 40 years of age, and prostate cancer mainly occurs in older men cause 90 % in those above sixty-fve.Objective. The main objective of this paper is to investigate the relationship between ovarian and prostate cancer with the BRCA1 and BRCA2 genes.Material and Methods. The ovarian and prostate cancer mechanism is discussed in detail, and their preventive measures with screening techniques are also demonstrated. This systematic review collected the related articles from online databases using the key terms ovarian cancer, prostate cancer, BRCA genes, mutation, polymorphism, carcinoma, sarcoma, and genetic association.Results. Based on the obtained information, it is found that the BRCA genes are highly associated with prostate cancer in men, and in women, it is significantly linked with breast cancer than ovarian cancer.Conclusion. Therefore, early diagnosis and genetic testing for BRCA1&BRCA2 genes in both men and women are necessary. In some cases, these genes might even cause different types of cancer like pancreatic cancers. Identifying individuals with tumour-HRD through mutations in the homologous repair pathway and determining this gene expression is essential to improve treatment techniques developed during the previous decade and rapidly make their way into clinical trials practice. However, the safe introduction of these medicines into everyday practice will require a thorough understanding of treatment targets and associated adverse effects.